Knowledge, attitude, and perception of dental undergraduates towards mobile and digital learning methods in India: A cross-sectional study - Anshu Prakash; Kumar Anand; Amit Kumar; Ritesh Raj; Santosh Anand; Kriti; Shiwangi Singh (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Internet-based education is having few advantages since it increases an emphasis on the education system based on problems by incorporation of both visual as well as interactive tools. Also, some contributions to practical skills can be made using pictorial as well as video-based knowledge. The present study aimed to assess the knowledge, attitude, and perception of dental undergraduates towards mobile and digital learning methods in India. MATERIALS AND METHODS: This was a cross-sectional questionnaire-based study conducted after obtaining Institutional Ethical Review Board permission. Before commencing the study, the purpose of the study was explained to the study participants and written informed consent was obtained. About 200 undergraduate students of dentistry in a single institution were selected as a convenient sample. Information obtained from responses was entered into an Excel sheet (Microsoft Corporation) and was further analyzed. Data collection was done for a period of one month. Statistical analysis: Obtained data were recorded and subjected to statistical analysis by use of statistical SPSS software (version 20.0, IBM). Descriptive statistical data were recorded as frequencies or percentages. Chi-square statistical test was used for the assessment of responses obtained from dental undergraduate students. The level of significance was fixed at a probability of <0.05. RESULTS AND OBSERVATIONS: On statistically analyzing, 99% of students were found to possess knowledge regarding the use of mobile phones for digital education. A good statistical correlation was obtained between attitude and perception regarding accessing digital learning using mobile phones. CONCLUSION: In the present study, good knowledge, attitude, and perception regarding the use of digital learning using phones were found among Indian dental undergraduates.